Proposed beginning reader in Pilipino for use in the Division of Isabela - Macabangun, Milagros Gatan 1931-
The aim of this study is to present a beginning reading which uses the phonetic approach, an approach proven very effective in teaching beginning reading in Pilipino. This study seeks to show how the mastery of letter-sound relationships can cut down the time spent in teaching children to learn to read. Furthermore, it presented ways of developing word perception, vocabulary and comprehension skills among very young learners through active involvement in a variety of exercises aimed at developing such skills.